PERAN PARA PIHAK TERHADAP KEBERLANJUTAN KESEPAKATAN KONSERVASI MASYARAKAT DI TAMAN NASIONAL LORE LINDU - Massiri, Sudirman Daeng; Nugroho, Bramasto; Kartodihadjo, Hariadi; Soekmadi, Rinekso (Universitas Tadulako, 2016)
Management of National Parks cause interdependence of many parties so that required appropriate institutional arrangements. However, the rules which have been designed in an institution often not implemented by stakeholders sustainably. This phenomenon occurs in Lore Lindu National Park (LLNP), in which property rights and the rules of Community Conservation Agreement (CCA) designed since the early 2000s is not implemented by stakeholders in LLNP. This problem situation suspected closely related to the interests, capacity, rights, responsibilities, revenues and relationship between stakeholders in the management of national parks. This research aimed to understand how the interests, capacity, rights, responsibilities, revenues and relationship of the stakeholders affected the performance of CCA. To achieve these objectives, this study was using a stakeholder analysis with 4RS framework (rights, responsibility, revenues and relationship) and analysis of access. This study used qualitative research methods with conduct interviews with key informants to obtain deeply explanation about the role the stakeholders in the agreement. The study found that the high interests of stakeholders to resources of LLNP were land, timber for local need, biodiversity, water and tourism. Local community have high capacity to access gain of resources in LLNP, while the high control access capacity in LLNP were LLNP officer, Village Chiefs, Customary Institutions in homogenous villages and Village Conservation Council/LKD in Rimba zone. However, they did not have high capacity of access maintenance for the use of forest resources. Imbalance of rights, responsibilities and revenues of stakeholders became one the constraints for the sustainability CCA. The relationship between local communities, local institutions to BBTNLL was categorized as poor, even though it has constructed efforts of conservation agreements